2013
DOI: 10.1021/om400649c
|View full text |Cite
|
Sign up to set email alerts
|

CH–NH Tautomerism in the Products of the Reactions of the Methanide [HC(PPh2NSiMe3)2] with Pnictogen and Tellurium Iodides

Abstract: The reactions of K[HC(PPh2NSiMe3)2] (K[1]) and MI3 (M = As, Sb) or TeI4 gave as the major products the complexes [{MI n }{C(PPh2NSiMe3)(PPh2NHSiMe3)}] (MI n = trans-AsI2, trans- or cis-SbI2, TeI3), which feature the ligand [C(PPh2NSiMe3)(PPh2NHSiMe3)]− (2). This anion, the NH tautomer of [HC(PPh2NSiMe3)2]−, is formally generated by a 1,3-hydrogen shift to give complexes in which the ligand is N,C-chelated to the main-group-metalloid center. The M–C distances are slightly longer than the sum of the covalent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Such a proton shift can be seen as a P analogue of the known imine−enamine tautomerism and has been described by most recent works published in the course of the preparation of this paper. 5 On consideration of the Lewis acidity of a coordinated element halide fragment to cause a proton shift, it is interesting that for smaller elements with potentially more Lewis acidic fragments such as [AlCl 2 ] + , [AlBr 2 ] + , and [GaCl 2 ] + , a N,Nchelating coordination mode forming a six-membered ring is adopted and no proton shift occurs. 4d,7 A somehow comparable shift has already been described for neutral bis-(iminophosphorane)methane ligands coordinating to transition m e t al s ( R h , I r , P t ) .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a proton shift can be seen as a P analogue of the known imine−enamine tautomerism and has been described by most recent works published in the course of the preparation of this paper. 5 On consideration of the Lewis acidity of a coordinated element halide fragment to cause a proton shift, it is interesting that for smaller elements with potentially more Lewis acidic fragments such as [AlCl 2 ] + , [AlBr 2 ] + , and [GaCl 2 ] + , a N,Nchelating coordination mode forming a six-membered ring is adopted and no proton shift occurs. 4d,7 A somehow comparable shift has already been described for neutral bis-(iminophosphorane)methane ligands coordinating to transition m e t al s ( R h , I r , P t ) .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The coordination geometry around bismuth in 2 as well as around antimony in 3 represents a distorted seesaw analogous to the reported "cis"-type complexes found for the trimethylsilyl-substituted derivatives, in which the [EX 2 ] + fragment features a bent alignment. 5 On the basis of a sole X-ray structure Chivers and Vargas-Baca et al found a symmetrically N,C,N-chelating coordination type for an almost linear [BiI 2 ] + fragment and applied quantum mechanical calculations to provide an explanation for the absence of the intramolecular 1,3-proton shift in the case of bismuth. In their findings the generally energetically favored CH tautomer of the ligand is overcompensated by a stabilizing interaction energy between the ligand anion and the metal fragment (for which only a linear arrangement was considered).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to the best of our knowledge, there is no species with four different pnictogens in one heterocycle. There are four reports on compounds including all four of the pnictogens N, P, As, and Sb, but among these, only [ClAs{μ‐(N‐PMe 3 ) 2 }SbCl 4 ] investigated by Dehnicke et al., is a molecular species …”
Section: Methodsmentioning
confidence: 99%
“…There are four reports on compounds including all four of the pnictogensN ,P ,As,a nd Sb, but among these, only [ClAs{m-(N-PMe 3 ) 2 }SbCl 4 ]i nvestigated by Dehnicke et al,i s am olecular species. [20][21][22][23] Recently,w ep repared the four-membered heterocycles [ClE(m-PTer)] 2 containing the heavy pnictogensE = P, As, Sb, Bi. [24] It is known that the supermesityl (Mes*)s ubstituent stabilize the monomeric species better than the dimer in heterocycles such as [ClE(m-NTer)] 2 compared to the terphenyls ubstitu-Scheme1.Synthesis of all pnictogen four-membered heterocycles.Scheme2.Selectedknown all pnictogen anionic analogs of allyl species.[a]Supporting information and ORCID(s)f rom the author(s) for this articleare available on the WWW under http://dx.…”
mentioning
confidence: 99%